Collection Practices and Socio-Economic Status of Crab Collectors at Shyamnagar Upazila, Satkhira Distrct in Bangladesh (Jagannath University Journal of Life and Earth Sciences, 2024)
This study evaluated the mud crab (Scylla olivacea)  collection techniques and socio-economic conditions of crab collectors in Shyamnagar Upazila. The results showed that 48% of the collectors collected crabs from the Sundarbans mangrove forest; on the other hand,  42% of the crab collectors collected crabs from coastal rivers, and 10% collected crabs from canals and shrimp farms. In the study area, 63% of crab collectors used doon with Cuchia fish as bait, 6.66% used thopa with Tilapia fish as bait, and the rest used net or hand-picking techniques to collect crabs. Most crab collectors were Muslims (56.9%), and the rest were Hindu (43.1%) regarding religious belief. Regarding gender, 58.1% of crab collectors were female, whereas 41.9% were male. Almost half of crab collectors (41.9%) had no institutional education. In this area, 33.72% were landless and lived on ‘Khas’ land. A significant number of people (29.5%)  were married at an early age. The crab collectors (36.2%) earned less than Tk. 200 daily. Natural calamities and other constraints are making the livelihood of crab collectors vulnerable, but they are trying to continue their occupation to sustain their lives.Jagannath University Journal of Life and Earth Sciences, 9(1): 57–68, 2023 (June)